PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2023 - Rindi Ramadhani; Muhammad Hasan Ma’ruf; Rukmini Rukmini (CV. Denasya Smart Publisher, 2024)
This study aims to conduct a test of the effect of good corporate governance mechanisms on the financial performance of banking companies. Financial performance is calculated using ROA. On the other hand, corporate governance mechanisms are calculated using the following variables: size of the board of commissioners, size of the board of directors, and size of the audit committee. The sample used in this study includes 84 banking companies listed on the Indonesia Stock Exchange (IDX) in 2021 to 2023. Sampling was carried out using the purposive sampling method. In this study, the analysis used is the multiple linear analysis technique. These findings show that the size of the board of commissioners does not affect the company's financial performance. Meanwhile, the board of directors and audit committee have an effect on the financial performance of banking companies.